Pre-extension demonstration and evaluation of food barley technology (Hordeum vulgare L.) in West and Kellem Wollega zones - Tasfa, Hika; Umar, Damaksa (Research in Agriculture Livestock and Fisheries, 2022)
Pre extension demonstration of food barley varieties was carried out during 2010/11 and 2011/12 E.C cropping season with the objective of evaluating the best performed and preferred food barley varieties under farmer’s management condition. The trial was carried out selecting one kebele from each Anfilo, Hawa Gelan and Boji Dirmaji districts and selecting two kebeles from Seyo district. Three improved varieties of food barley (dinsho, abdane and biftu) with a local check were evaluated with full participation of FRG members under their management condition. The best fit variety was selected with the participants. The total of five (5) FRGs which incorporated a total of 59 male and 23 female was established. Each experimental plot had gross area of 100 m2 and rows spacing of 25 cm were used. All recommended agronomic practices were equally applied to all plots. Yield of varieties were collected and analyzed using descriptive statistics. Accordingly the yield performances of varieties were 28.66 qt/ha, 26.02 qt/ha, 23.96 qt/ha and 21.15 qt/ha for Dinsho, Abdane, Biftu and local respectively. Accordingly, the yield advantage of dinsho over local is 35.5% while the yield advantage of abdane over local is 23.02% and yield advantage of biftu over local is 13.28%. Farmers were enhanced to evaluate the technology using their own criteria. Accordingly they selected dinsho variety as their first choice by its grain yield, disease resistance, finger size and abdane variety secondly by its merits of early maturity, lodging tolerance and biftu and local thirdly and fourthly respectively. Generally based on farmer’s preference and objectively measured trait variety dinsho should be scaled up/out in Sayo, Hawa Galan, Anfilo and Bodji Dirmaji districts and similar agro ecology of West and Kellam wollega zones. Res. Agric., Livest. Fish.9(1): 29-36, April 2022